How Does the Romanian Ministry of Education Distribute Doctoral Grants Towards Public Universities? A statistical exploration of an institutional black-box - Adrian Hatos (University Babes-Bolyai, 2018)
This study attempts to clarify the logic behind the allocation of doctoral grants between 2012 and 2016 in Romania, based on statistical data regarding the cohorts of doctoral students and of doctoral supervisors available in official reports and in the Ministry's statistical data. After analysing the correlations of the doctoral grant distributions for first year admissions from the autumn of 2014, the study concludes that neither the offer nor the demand of doctoral students justify the decisions of the responsible Minister to the extent in which this is justified by the distribution following the 2011 classification of universities and the subsecquent correction of 2012, following the change of the majority in power. To this, individual variations are added, whose logic is not explained by any of the variables included in this analysis, namely the position held in the university classification, the number of doctoral supervisors and the number of doctoral students.